2010
DOI: 10.1016/j.nut.2010.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Fructose and metabolic diseases: New findings, new questions

Abstract: There has been much concern regarding the role of dietary fructose in the development of metabolic diseases. This concern arises from the continuous increase in fructose (and total added caloric sweeteners consumption) in recent decades, and from the increased use of high-fructose corn syrup (HFCS) as a sweetener. A large body of evidence shows that a high-fructose diet leads to the development of obesity, diabetes, and dyslipidemia in rodents. In humans, fructose has long been known to increase plasma triglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
222
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(244 citation statements)
references
References 79 publications
8
222
0
6
Order By: Relevance
“…Studies show that added sugar (over-) consumption, specifically in the form of sugar-sweetened beverages (SSB), seems to be linked to different harmful health outcomes such as obesity and diabetes (3)(4)(5) . SSB may also potentially increase the risk of CVD through their high amount of rapidly absorbable carbohydrates that may, via an elevated hepatic de novo lipogenesis, result in hypertension, accumulation of visceral and ectopic fat, and increased TAG and LDL cholesterol (LDL-C) and decreased HDL cholesterol (HDL-C) levels (6,7) . The increased glycaemic load caused by a high SSB intake may lead to inflammation, β-cell dysfunction and insulin resistance, as suggested by who, in their pooled meta-analysis from three prospective cohorts, reported that participants in the highest category of SSB intake had a 20 % greater risk of developing metabolic syndrome than those in the lowest category of intake (4) .…”
mentioning
confidence: 99%
“…Studies show that added sugar (over-) consumption, specifically in the form of sugar-sweetened beverages (SSB), seems to be linked to different harmful health outcomes such as obesity and diabetes (3)(4)(5) . SSB may also potentially increase the risk of CVD through their high amount of rapidly absorbable carbohydrates that may, via an elevated hepatic de novo lipogenesis, result in hypertension, accumulation of visceral and ectopic fat, and increased TAG and LDL cholesterol (LDL-C) and decreased HDL cholesterol (HDL-C) levels (6,7) . The increased glycaemic load caused by a high SSB intake may lead to inflammation, β-cell dysfunction and insulin resistance, as suggested by who, in their pooled meta-analysis from three prospective cohorts, reported that participants in the highest category of SSB intake had a 20 % greater risk of developing metabolic syndrome than those in the lowest category of intake (4) .…”
mentioning
confidence: 99%
“…9 This may reflect different types of fruit and/or vegetables consumed by different Table 4 Association between portions of fruit or of vegetables consumed and risk of death, from all causes unless specified populations, and merits further consideration, particularly given current interest in the role of fructose in driving obesity. [29][30][31] When individual types of fruit and vegetables were examined, portions of fresh vegetable, salad, fresh and dried fruit showed significant negative associations with all-cause mortality. It has been suggested that some fructose consumption in levels provided by fruit may be beneficial for glycaemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Doubling agricultural productivity (2.3) could constrain the reduction of premature mortality from non-communicable diseases (3.4) if this increase focuses on lownutrient and energy-rich foods, such as cereals, tubers, and fats. These agricultural products are contributing to the triple burden of undernutrition, micronutrient deficiency, and obesity with its associated health issues, such as stunting, anaemia, and diabetes (Tappy et al, 2010). The poor are adversely affected in this respect because energy-rich, low-nutrient foods are becoming more affordable to them worldwide (Bernard, 2015).…”
Section: Key Interactionsmentioning
confidence: 99%